How does education affect knowledge and intergenerational social class mobility in China? - Bingqiang Li; Wenjie Nie; Xuan Zuo; Heping Zuo (Journal of Innovation & Knowledge (JIK), 2025)
Education is an important tool used to equip knowledge and pursue self-improvement, which may affect intergenerational social class mobility through human capital accumulation. Using 8014 mixed cross-section samples from the 2017, 2018 and 2021 China General Social Survey (CGSS), an multi-nominal logistic regression model was adopted to empirically analyse the impact of educational levels on intergenerational social class mobility in China. The econometric results indicated that (1) higher education considerably promotes subjective and objective upwards intergenerational social class mobilities, with the objective effect exceeding the subjective effect by 3.4 %; (2) the implementation of the compulsory education law and the expansion of higher education enrolment has increased the potential for high educational level to drive upwards intergenerational social class mobility; (3) among the different types of education, population migration exerts a repelling effect on objective upwards intergenerational social class mobility, whereas family background exerts a negative effect on subjective intergenerational social class mobility; and (4) the effects of education on intergenerational social class mobility are heterogeneous, with women, non-agricultural hukou holders and groups in developed areas facing greater difficulties in achieving social mobility through education. The main contribution of this study is its initial detection of the varying impacts of educational level on intergenerational social class mobility, as investigated through subjective and objective perspectives.
Keywords: C50; I24; J01; 650; Education; Class; Intergenerational mobility; Intergenerational transmission